Career Management in Digital Transformation for Employee Wellbeing: A Systematic Literature Review - Lesmana, Angga; Nur Wening; Rian Oktafiani (Journal of Business and Management Review, 2025)
Research Aims: to examine how career management and employee well-being are related and to emphasize the critical role that career management plays. Design/methodology/approach: This study gathered 201 articles from Scopus-indexed journals between 2015 and 2025 and examined 12 of them using a systematic literature review methodology. Research Findings: The findings demonstrated that employees' subjective well-being, work engagement, and career satisfaction are positively impacted by successful career management practices, such as job designing, career skill development, and career adaptability. However, there is the discrepancy between theory and practice, especially in the implementation of career strategies that support digital skills needs in organizations. In addition, career development programs such as careers skill have been shown to increase employees' self-efficacy and resilience in the face of change. Theoretical Contribution/Originality: pointing out the gap between theory and reality in digital career management and suggesting a comprehensive strategy to address how career management affects workers' well-being. The studies have important implication for human capital managers as they create career management policies and procedures to enhance workers' well-being during the digital transformation.